2015
DOI: 10.5941/myco.2015.43.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Three New Records of Mortierella Species Isolated from Crop Field Soil in Korea

Abstract: Three new fungal species of the genus Mortierella, Mortierella zychae, Mortierella ambigua, and Mortierella indohii, have been reported in Korea. The fungi were encountered during a study on the fungal community of soil samples collected from different locations in Korea. The species were identified based on molecular and morphological analyses. This study presents detailed descriptions of the morphological observations and molecular phylogenetic analysis of these three fungi. All three species were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Fewer details of metabolism and ecology are available for non-pathogenic fungal indicators. Mortierella , the most common genus among fungal indicators in this study, are known to be a large genus of saprotrophs [55]. Exophiala equina and Didymella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer details of metabolism and ecology are available for non-pathogenic fungal indicators. Mortierella , the most common genus among fungal indicators in this study, are known to be a large genus of saprotrophs [55]. Exophiala equina and Didymella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades numerous studies indicated the occurrence of Mortierella species in diversified environments, e.g., rocks, caves, mines, asbestos fibers, rivers, lakes, plant tissues soils, and rhizospheres (including agricultural areas) at each latitude [4][5][6][7][8][9]. Recently, researches employing molecular methods revealed that not only the Aspergillus and Penicillium genera, but also Mortierella strains are the most abundant filamentous fungi in the soils around the world [10][11][12][13][14][15][16]. Moreover, the Mortierella omnipresence may be confirmed by in the environment the effects of 35-year application of an organic fertilizer to the agricultural soil in China (Anhui Province) in order to promote plant growth.…”
Section: From the Pioneering Microorganisms To The Important Agricultural Inoculants 21 Isolation And Identification Of Mortierella Spp Fmentioning
confidence: 99%
“…In turn, filamentous fungi with asseptate hyphae (coenocytic hyphae) belong to the Mortierellales order. Mortierella species form colonies often described as pale white, white or whitish (sometimes little dark whitish at the center) zonate, forming a typical rosette pattern [7,8,15,18,19]. In the course of time, the reverse side of the colonies may become yellowish.…”
Section: From the Pioneering Microorganisms To The Important Agricultural Inoculants 21 Isolation And Identification Of Mortierella Spp Fmentioning
confidence: 99%
“…In addition to Penicillium and Aspergillus genera , Mortierella are very common filamentous fungi isolated from the environment [ 1 , 2 ]. The studies on soil ecology describing fungal diversity reported an occurrence of Mortierella strains in soil, rhizosphere, rivers, and lakes on different continents [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%